IMF effects on short-period fluctuations at low latitudes - Agarwal, A.K.; Nityananda, N.; Singh, B.P.; Rastogi, R.G. (My University, 1978)
The Influence of the north–south component (B z) of the interplanetary magnetic field (IMF) on geomagnetic activity is well established1,2, although a search for closer links between them has encountered some difficulties because magnetospheric responses depend on many parameters. It is also expected that the effects would be dominant at high or auroral latitudes. These studies are important because the B z component controls the transfer of energy carried by the solar wind into the magnetosphere and consequently into the lower atmosphere, a phenomenon which has gained considerable importance in solar–terrestrial relationships. Here we investigate the effect of B z variations at low latitudes particularly the equatorial region, which is relatively free from particle precipitation. Furthermore, due to the high electrical conductivity of the ionosphere during the daytime over this region, variations near the magnetic equator are very sensitive to changes in the electric field. Thus, equatorial stations may reveal some new features of the correlations between geomagnetic variations and the IMF.
Keywords: Interplanetary magnetic fields; Geomagnetic activity; Geomagnetic variations; Low latitudes; IMF